PSIKOEDUKASI: MENGHIDUPKAN HARAPAN (HOPE) DAN OPTIMISME DALAM MENETAPKAN TUJUAN HIDUP BAGI SISWA MAN 4 BEKASI - Adinda Putri Dewi; Ajeng Cahya Lestari; Ira Dinanti Hariyanto; Wanda Fitri Berliana; Zahra Permata Sari (CV. ADIBA AISHA AMIRA, 2025)
This psychoeducation aims to improve the understanding, attitudes, and skills of adolescents in building hope and optimism as a foundation in designing life goals. This activity was carried out on 30 students of MAN 4 Bekasi using a quantitative-descriptive approach. The implementation method includes lectures, discussions, and pre-tests and post-tests to measure changes in participants' understanding. The results showed an increase in knowledge scores and positive changes in students' ways of thinking and behavior. Participants began to understand the difference between hopes and desires, and were able to formulate realistic goals and strategies for achieving them. They also showed improvements in emotional regulation, social support, and more adaptive self-reflection. Although the increase in scores was not statistically significant, qualitative changes showed internalization of important values. This activity emphasizes the importance of psychoeducation in shaping adolescent psychological resilience amidst life's challenges. In the future, similar programs are expected to be developed more widely and sustainably.